Single Nucleotide Polymorphism within the Promoter Region of Cynomolgus Monkey LDLR Gene - Achmad, Taher; Solihin, Dedy Duryadi; Sulistiyani, Sulistiyani; Astuti, Dewi Apri; Sajuthi, Dondin (Makara Journal of Science, 2018)
The cynomolgus monkey (Macaca fascicularis) is one of the most common nonhuman primates used as an animal model in biomedical research related to atherosclerosis. However, little is known about genetic variation in the low density lipoprotein receptor (LDLR) gene, its effect on cholesterol levels, and associated risks of atherosclerosis. There-fore this study aimed to identify genetic polymorphisms, namely single nucleotide polymorphisms (SNPs), within the promoter region of LDLR and their relationship with animal responsiveness to hypercholesterolemia due to an atherogenic diet. In this research, SNPs were studied using DNA isolated from22 cynomolgus monkeys obtained from aprevious study, consisting of two hyporesponders, 19 hyperresponders, and one extremecase. The result showed that two SNPs existed in the promoter region, namelyg.−169T>C and g.−265G>A. SNP g.−265G>A showed linkages with extreme responsiveness and can be used as a potential genetic marker for extreme animals. The result of this study has extended our knowledge of polymorphism in the LDLR geneand its use intheselection of cynomolgus monkeys as animal models in research on hypercholesterolemia and atherosclerosis.